Wyzwania stojące przed polską polityką rozwoju regionalnego - Rogowska, Małgorzata (Challenges for polish regional development policy, 2006)
The article concerns the problem of regional policy and its development in Polish conditions. This issue is given some special interest not only in Poland. Polish accession to EU structures opens the period where forceful and efficient regional policy is percieved as a big chance for Polish regions, especially localized in the eastern part ofthe country. The author aims to describe and formulate the most important challenges for Polish regional developmet policy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 87-94